How demography affects asset characteristics in Hungary - Posza, Alexandra; Csapi, Vivien (Marketing & Menedzsment, 2021)
THE AIMS OF THE PAPER The population factor in general influences most of the global megatrends. While it was considered one of the major driving forces for economicgrowth in the 20th century, it has become the greatest risk factor for the socio-economic landscape. Hungary is experiencing one of the fastest demographic transitions in Europe. Due to the continued extension of longevity and the steep decline in fertility rate, the size and percentage of theelderly population (i.e., aged 65 and above) rapidly increased during the last decades. The paper aims to examine whether population ageing has an effect on asset prices in Hungary. METHODOLOGY The life cycle theory for Hungary was applied while exploring the quantitative link between population structures and asset prices, particularly onstock and bonds. In this study, the relationship between Hungary’s demographic characteristics and asset class returns will be examined by reviewing previous academic and policy studies through conducting a regression analysis of bond yields and P/E ratio of BUX Index related to demographic variables. MOST IMPORTANT RESULTS The connection between stock prices and demographic trends is impacted by the life cycle theory of asset accumulation/decumulation and portfolio choice. In Hungary, the younger adults between 36 and 45, and the classic middle-aged individuals are in their peak savings years and invest heavily in stocks, driving up stock prices. The old-aged individuals decumulate assets and sell stocks to finance their retirement, depressing stock prices. In addition, the investors become more risk-averse and prefer fewer holdings of stocks as they grow older. The Middle/Old ratio and the BUX P/E ratio have a strong positive correlation during the period 1995-2020. The bond yields show a similar connection with the Yuppie/Nerd ratio. The results of demographic variables predicting bond-yields are strong and proving the international patterns. RECOMMENDATIONS The paper highlighted that the demographic variables are not only appropriate for socio-demographic analysis since the members of the different age groups have their own consumption, saving and investing characteristics that can have an impact on the asset prices besides other commonly usedparameters. Acknowledgements: This article was supported by EFOP3.6.116201600004 that has been entitled ‘Comprehensive developments at the University of Pécs for smart specialization’. (Project element ‘Decisionmaking at older ages’, topic no. 11)